Design, delivery, and evaluation of seminars and hands-on courses worldwide on intraoperative imaging in orthopedic trauma. Issue 11 (November 2021) - Vetter, Sven Yves; Kraus, Michael; Rikli, Daniel; Pesantez Hoyos, Rodrigo; Grützner, Paul Alfred; Cunningham, Michael; Bolliger, Bettina; Ghidinelli, Monica; Franke, Jochen
Highlights: Delivery of case-based intraoperative imaging seminar and course in orthopaedic surgery. Reduction of knowledge gaps for participants of the intraoperative imaging seminar/course. Intraoperative imaging seminar and course help to address educational needs for residents and complement existing concepts. Abstract: Introduction: Although intraoperative imaging is important for assessing the quality of several steps during fracture fixation, most trainees and surgeons have received little formal education on this topic and report they learn "on the job" and "through practice". A planning committee of orthopedic trauma surgeons was established to design a curriculum using "backward planning" to identify patient problems, identify gaps in surgeons' knowledge and skills, and define competencies as a framework for education in order to optimize patient care. Materials and methods: The committee defined 8 competencies related to intraoperative imaging, with detailed learning objectives for each one (e.g. select the imaging modality, set up the operating room). An interactive, case-based half-day seminar to deliver these objectives for 2-D and 3-D intraoperative imaging during the fixation of common fractures was designed. The seminar was delivered in several locations worldwide over a 6-year period and evaluation and assessment data were gathered online. A full-day procedures course was added and delivered 6 times to address the skills component of competencies. Results: 17 seminars and 6 courses were delivered and attended by an average of 26 and 17 participants respectively (ranges 13–42 and 13–20). Pre-event gap analysis and assessment question scores confirmed needs and motivation to learn in all events. 97% of the 442 seminar participants and 98% of the 100 course participants would recommend the events to colleagues. An average of 88% and 90% respectively learned something new and plan to use it in their practice (range 63%-100%). Commitment to change (CTC) statements showed intended practice improvements related to all competencies. Discussion: The large percentages of high impact ratings for all events suggest the content met the needs of many participants. Post-event reduction in gap scores and an increase in the desired level of ability for most competencies suggests the content addressed many gaps. Conclusions: Case-based, interactive seminars and courses addressing knowledge, skills, and attitudes to optimize the use of intraoperative imaging during the fixation of common fractures help address unmet educational needs for trainees and complements existing formal training.